Al-Ibtikar fi Ta'lim al-Lughah al-'Arabiyyah min Khilal Wasilah Qalam AI: Juhd li Tarqiyah Qawa'id al-Imla' li al-Tullab - Roudhotul Jannah; Abdul Ghofur (`A Jamiy : Jurnal Bahasa dan Sastra Arab, 2026)
يهدف هذا البحث إلى تحديد مدى فعالية ترقية قواعد الإملاء من خلال وسيلة Qalam AI لطلاب الفصل العاشر بالمدرسة العالية الحكومية الواحدة جومبانج. خلفية هذا البحث هي أن العديد من الطلاب يواجهون صعوبة في تطبيق قواعد الإملاء في درس مهارة الكتابة، مثل كتابة الحروف العربية بشكل خاطئ وعدم القدرة على التمييز بين أصوات الحروف العربية المتشابهة والإهمال في وضع علامات الحروف المتحركة أو صعوبة فهم قواعد الإملاء نفسها. تكمن حداثة هذا البحث في استخدام وسيلة Qalam AI في تعليم قواعد الإملاء لطلاب المدرسة العالية، وهو موضوع لم يُبحث فيه كثيرًا في الدراسات السابقة التي ركزت بشكل عام على وصف لمزايا وعيوب وسيلة Qalam AI والقراءة. استخدم هذا البحث منهجًا كميًا بتصميم ما قبل التجربة في شكل تصميم ما قبل الاختبار وما بعد الاختبار لمجموعة واحدة. كانت عينة البحث 30 طالبًا من الفصل العاشر بالمدرسة العالية الحكومية الواحدة جومبانج. تم جمع البيانات من خلال الاختبار القبلي والاختبار البعدي الذي يتألف من 10 أسئلة من أصل 20 سؤالاً تم اختبار صدقيتها وثباتها حول مادة قواعد الإملاء التي تم تدريسها تحت موضوع الهواية. أُجري تحليل البيانات باستخدام اختبار الصدق والثبات للأداة، واختبار Shapiro-Wilk للطبيعية، واختبار Wilcoxon Signed Rank Test لاختبار الفرضية. وأظهرت النتائج أن أداة الاختبار صدق وثبات، وأن بيانات الاختبار القبلي والبعدي كانت موزعة بشكل غير طبيعي. أظهرت نتائج اختبار ويلكوكسون للرتب الموقعة أن غالبية الطلاب قد ترقيت قدراتهم في قواعد الإملاء بعد استخدام وسيلة Qalam AI، حيث ارتفعت درجات 24 طالبًا، وانخفضت درجات 3 طلاب، وظلت درجات 3 طلاب دون تغيير. تبلغ قيمة الدلالة الإحصائية (ثنائية الذيل) 0,000 < 0,05، مما يشير إلى قبول الفرضية البديلة ورفض الفرضية الصفرية. وهذا يعني أن هناك ترقية ذات دلالة إحصائية بعد استخدام وسيلة Qalam AIلطلاب الفصل العاشر بالمدرسة العالية الحكومية الواحدة جومبانج. ولكن هذا البحث له أيضًا قيود لأنه استخدم مجموعة واحدة فقط، وهي المجموعة الضابطة. الكلمات المفتاحية: الوسيلة التعليمية; Qalam AI ;قواعد الإملاء This study aims to determine the effectiveness of improving qawa’id imla’ through the Qalam AI platform among 10th-grade students at MAN 1 Jombang. The background of this study is that many students experience difficulties in applying spelling rules in writing skills instruction, such as misspelling Arabic letters, being unable to distinguish between similar Arabic letter sounds, being careless in placing diacritics, or having difficulty understanding the spelling rules themselves. The novelty of this study lies in the use of the Qalam AI platform for teaching spelling rules to high school students, an area that has received little attention in previous research, which has generally focused on description of the advantages and disadvantages of the Qalam AI platform and reading. This study employed a quantitative approach with a pre-experimental design in the form of a One-Group Pretest-Posttest Design. The research subjects were 30 10th-grade students from MAN 1 Jombang. Data were collected through pre-tests and post-tests consisting of 10 items selected from a set of 20 questions that had been validated and found to be reliable regarding the spelling rules (qawa’id imla’) taught under the theme of al-hiwayah. Data analysis was conducted using instrument validity and reliability tests, the Shapiro-Wilk normality test, and the Wilcoxon test for hypothesis testing. The results showed that the test instrument was valid and reliable, and that the pretest and posttest data were not normally distributed. The results of the Wilcoxon Signed-Rank Test indicate that most students showed an improvement in their spelling skills after using the Qalam AI platform, with 24 students showing an increase in their scores, 3 students showing a decrease, and 3 students maintaining the same score. The value of Asymp. Sig. (2-tailed) is 0.000 < 0.05, indicating that Ha is accepted and H0 is rejected, meaning there was a statistically significant improvement following the use of Qalam AI among 10th-grade students at MAN 1 Jombang. However, this study also has limitations because it used only one group, namely the control class. Keywords: Learning Medium; Qalam AI; Qawa’id Imla’ Abstrak Penelitian ini bertujuan untuk mengetahui efektivitas penggunaan media Qalam AI untuk meningkatkan qawa’id imla’ siswa kelas X MAN 1 Jombang. Penelitian ini dilatarbelakangi oleh rendahnya kemampuan siswa dalam menerapkan qawa’id imla’ pada pembelajaran maharah kitabah, yang ditandai dengan kesalahan penulisan huruf hijaiyah, kesulitan membedakan bunyi huruf yang serupa, ketidaktepatan penempatan harakat, serta lemahnya pemahaman kaidah imla’. Kebaruan penelitian ini terletak pada pengujian efektivitas penggunaan Qalam AI sebagai media pembelajaran qawa’id imla’ di tingkat Madrasah Aliyah, sedangkan penelitian sebelumnya lebih banyak berfokus pada deskripsi manfaat dan kekurangan media atau keterampilan membaca bahasa Arab. Penelitian ini menggunakan pendekatan kuantitatif dengan desain pre-eksperimental berupa one group pretest-posttest design. Subjek penelitian terdiri atas 30 siswa kelas X MAN 1 Jombang. Instrumen penelitian berupa 20 soal pilihan ganda yang diuji validitas dan reliabilitasnya, dan diperoleh 10 butir soal yang dinyatakan valid untuk digunakan pada pretest dan posttest. Analisis data menggunakan uji Shapiro-Wilk dan uji Wilcoxon Signed Rank Test. Hasil penelitian menunjukkan bahwa 24 siswa mengalami peningkatan, 3 siswa mengalami penurunan, dan 3 siswa tidak mengalami perubahan. Hasil uji Wilcoxon menunjukkan nilai Asymp. Sig. (2-tailed) sebesar 0,000 < 0,05 yang berarti terdapat peningkatan yang signifikan secara statistik setelah penggunaan Qalam AI. Penelitian ini memiliki keterbatasan karena hanya menggunakan satu kelompok tanpa kelompok kontrol sehingga generalisasi hasil masih terbatas. Kata Kunci: Media Pembelajarn; Qalam AI; Qawa’id Imla’